Respostas

2014-08-06T23:45:27-03:00
X=7-2y

7-2y-2y=-5
7-4y=-5
-4y=-5-7
-4y=-12
y=-12/-4
y=3

S¹= {3,1}
2 1 2
A melhor resposta!
2014-08-06T23:46:38-03:00
 1 sistema:x = 7 - 2y
colocando no segundo sistema:  ( 7 - 2y ) - 2y = -5
                                                     7 -4y = -5
                                                      -4y= -5 + -7 . (-1)
                                                        y= 12 /4  
                                                         y= 3 
recolocando no 1 sistema; x + 2 (.3) = 7
                                          x =7 - 6
                                            x= 1
1 5 1